Existence of coupled coincidence best proximity point - Pulak Konar; Sumit Chandok (Surveys in Mathematics and its Applications)
This work of optimality is engaged with couple coincidence best proximity point. We have developed some optimal results where control functions and non-linear weak inequalities are evident. Further using our results, we establish some fixed point results. Our work is supported by an illustration.